Approximation and comparison in word-formation: The case of denominal adjectives in Dutch, German, and English - Matthias Hüning; Barbara Schlücker (Zeitschrift für Wortbildung)
The paper presents a corpus-based comparative study of denominal adjectives in Dutch, German, and English. It aims at clarifying the notion of approximation. More specifically, it focuses on investigating the relation between approximation and comparison as semantic categories in word-formation. Drawing on equivalent patterns, we study both the relation between comparative and approximative readings in various word-formation patterns (derivation and compounding) in Dutch, German, and English as well as the respective differences between the languages. We specifically focus on suffixes and other right head constituents (in particular Dutch -achtig, German -artig and -ähnlich, and English -like), thereby addressing the question whether word class changing morphology is at all suitable for expressing approximation. We conclude that the patterns investigated in our study may have approximative readings but are not approximative in the strict sense.